DEVELOPING VR-ASSISTED RME LEARNING MEDIA TO IMPROVE STUDENTS’ CREATIVE THINKING SKILLS IN GEOMETRY - Ramadhani, Ravi Akmar; Rahmawati, Noviana Dini; Prayito, Muhammad (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Students’ creative thinking in mathematics remains a challenge, particularly in learning three-dimensional geometry. This problem is related to the abstract nature of the material and the limited use of interactive media in classroom instruction. This study aimed to develop and evaluate Virtual Reality (VR)-assisted learning media integrated with the Realistic Mathematics Education (RME) approach to enhance students’ creative thinking skills. The study employed a Research and Development design using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The participants were 64 ninth-grade students of SMP Negeri 9 Semarang, divided into an experimental group and a control group, with 32 students in each group. Data were obtained through expert validation sheets, student response questionnaires, and a creative thinking test. The findings showed that the developed media met the criteria of high validity, with media expert scores ranging from 92% to 93% and material expert scores ranging from 92% to 96%. Student responses also indicated that the media was practical, with a percentage of 80%. In addition, the experimental group achieved a higher mean score (83.50) than the control group (72.35). The independent samples t-test further revealed a significant difference between the two groups (p < 0.001). These results indicate that VR-assisted learning media integrated with the RME approach is valid, practical, and effective in improving students’ creative thinking skills. Kemampuan berpikir kreatif siswa dalam pembelajaran matematika masih menjadi tantangan, terutama pada materi geometri tiga dimensi. Kondisi ini berkaitan dengan sifat materi yang abstrak dan belum optimalnya penggunaan media pembelajaran interaktif di kelas. Penelitian ini bertujuan untuk mengembangkan dan mengevaluasi media pembelajaran berbantuan Virtual Reality (VR) yang diintegrasikan dengan pendekatan Realistic Mathematics Education (RME) untuk meningkatkan kemampuan berpikir kreatif siswa. Penelitian ini menggunakan metode Research and Development dengan model ADDIE yang meliputi tahap analysis, design, development, implementation, dan evaluation. Subjek penelitian berjumlah 64 siswa kelas IX SMP Negeri 9 Semarang yang dibagi ke dalam kelas eksperimen dan kelas kontrol, masing-masing sebanyak 32 siswa. Data dikumpulkan melalui lembar validasi ahli, angket respons siswa, dan tes kemampuan berpikir kreatif. Hasil penelitian menunjukkan bahwa media yang dikembangkan memenuhi kriteria sangat valid, dengan skor validasi ahli media sebesar 92%–93% dan ahli materi sebesar 92%–96%. Respons siswa juga menunjukkan bahwa media berada pada kategori praktis dengan persentase 80%. Selain itu, rata-rata skor kelas eksperimen (83,50) lebih tinggi dibandingkan kelas kontrol (72,35). Hasil uji independent samples t-test menunjukkan adanya perbedaan yang signifikan antara kedua kelas (p < 0,001). Dengan demikian, media pembelajaran berbantuan VR yang terintegrasi dengan pendekatan RME dinyatakan valid, praktis, dan efektif dalam meningkatkan kemampuan berpikir kreatif siswa.